Comparative risk of adverse perinatal outcomes associated with classes of antiretroviral therapy in pregnant women living with HIV: systematic review and meta-analysis - Beck, Katharina; Cowdell, Imogen; Portwood, Clara; Sexton, Harriet; Kumarendran, Mary; Brandon, Zoe; Kirtley, Shona; Hemelaar, Joris (Frontiers in Medicine, 2024)
30 cohort studies published in 2006-2022, including 222,312 pregnant women, met the eligibility criteria. Random-effects meta-analyses found no evidence that INSTI-ART is associated with adverse perinatal outcomes compared to NNRTI-ART and PI-ART. We found that PI-ART is associated with a significantly increased risk of SGA (Risk Ratio (RR) 1.28, 95% confidence interval (95% CI) [1.09, 1.51], p=0.003) and VSGA (RR 1.41, 95% CI [1.08, 1.83], p=0.011), compared to NNRTI-ART. Specifically, lopinavir/ritonavir (LPV/r) was associated with an increased risk of SGA (RR 1.40, 95% CI [1.18, 1.65], p=0.003) and VSGA (RR 1.84, 95% CI [1.37, 2.45], p=0.002), compared to efavirenz, but not compared to nevirapine. We found no evidence that any class of ART or specific 'third drug' was associated with an increased risk of PTB.Our findings support the recommendation of INSTI-ART as first-line ART regimen for use in pregnant WLHIV. However, the increased risks of SGA and VGSA associated with PI-ART, compared to NNRTI-ART, may impact choice of second-and third-line ART regimens in pregnancy. PROSPERO registration, CRD42021248987.